Первое правило королевы: [роман] / Татьяна Устинова - Устинова Татьяна Витальевна (Русский бестселлер, 2003)
Экземпляры: аб. ЦБ (20182106) / Инвентарный номер: 4556 / Цена: / Авт.знак: У80 / ББК: 84(2Рос)